Asuransi Jiwa Syariah Analisis Hajiyat Dalam Maqashid Asy-Syariah - Muhammad, Jaidatul Fikri; Nasution, Adelina; Suryani, Sitti (IAIN Langsa, 2023)
Abstract This article discusses the prospects and interest of the Indonesian people in sharia life insurance, the development of sharia life insurance which fluctuates and continues to compete with conventional life insurance. The writer then examined this sharia life insurance law using maqashid sharia analysis with the hajjiyat approach. In this case, caution is needed in using this ijtihad method so that the religious law (ijtihad law) that is issued in the fatwa produces laws that are accurate, proportional, acceptable and responsible. This research uses a qualitative research method with a conceptual approach. The concept that we want to analyze here is maqashid sharia by focusing on mashlahah hajjiyat, which means the author wants to research sharia life insurance in its legal status using hajjiyat analysis where hajjiyat is the second level of mashlahah after dharuriyat namely the aim of the law in seeking convenience and eliminating difficulties. If it is related to sharia life insurance, it eliminates difficulties for participants or heirs of sharia life insurance when they experience an accident or disaster to their life, whether illness or death, by making it easier to finance medical treatment, as well as for the heirs who are left behind in fulfilling their livelihood, education costs and even business capital. . The aim of this research is to act as a scientific treasure and be one solution to eliminate the anxiety and confusion of some Muslims regarding the legal status of life insurance, which some scholars consider the law is still controversial.